An overview of the use of dental floss in Pediatric Patients at the Baiturrahmah Dental Hospital - Lusy Noferike; Sri P. Utami (DiscoverSys Inc., 2022)
Objective: The purpose of this study was to determine the description of the use of dental floss in pediatric patients in the Baiturrahmah Dental Hospital.Material and Methods: This type of research is quantitative with a categorical descriptive method with a cross sectional research design. The population was pediatric patients who visited the pediatric patients in the Baiturrahmah Dental Hospital in July 2020. Sampling in this study used the total sampling method. characteristics of the frequency of use of dental floss in children in the pediatric patients in the Baiturrahmah Dental Hospital, Padang. Results: Showed that the average children in the pediatric patients in the Baiturrahmah Dental Hospital, Padang, were 38.2% not independent in brushing their teeth, 3.9% were not disciplined in using dental floss and 48.7% of parents did not care about bringing their children to the doctor. teeth and 63.2% lack discipline in using dental floss.Conclusion: Educational institutions are expected to provide education to all their students about the importance of maintaining oral hygiene and so that students understand the importance of oral health.